The Activities in the West in the 1940s to Free Lithuania: the Lithuanian American Council in 1940–1950 - Banionis, Juozas (Genocidas ir rezistencija, 2006)
In the 1940s, when Lithuania and the other Baltic states were occupied, the old Lithuanian émigré community in the USA was the first to defend Lithuania's independence and freedom in the West. On 10 August 1940, the main Lithuanian political organisations, supported by the Roman Catholic Federation of Lithuanian Americans, established the Council to Aid Lithuania (LGT) in Pittsburgh in Pennsylvania. Leonardas Šimkus became the chairman of its General Board. It was the first organisation in Lithuania's resistance struggle against the Soviet occupation. On 15 October 1940, at a reception of a delegation from the council in the White House, President F. D. Roosevelt made his historical statement about the suspension of Lithuania's independence, which gave Lithuanians in the West a new impulse for their political activities.The council, which combined the main political trends among Lithuanian Americans (Catholic, socialist and nationalist), formed the Lithuanian American Council (ALT) on 15 May 1941. Its main objective was to coordinate the activities for Lithuania's liberation in democratic countries in the West.Because of the negative attitude to the years of Antanas Smetona's presidency, the tautininkai (nationalists) broke away from the council on 7 June 1941, and established the League for the Liberation of Lithuania (LVS), which on 6 February was reorganised into the American Lithuanian Mission (ALM). This organisation was in opposition to the ALT until the return of the imaininkai on 7 November 1947.The first Lithuanian American Congress, which was held on 2 and 3 September 1943, established guidelines for further activities by the ALT: to organise aid for Lithuanians who had suffered in the war, and to see that the principles of the Atlantic Charter were applied to Lithuania. In order to attain these objectives, the Baltic American Freedom Foundation was established on 25 March 1944 (BALF, under its chairman Juozas Končius). The foundation was concerned only with relief activities. In order to further the formation of a favourable opinion of the American administration and the general public about Lithuania’s liberation, the Lithuanian Information Center (LAIC, headed by Kostas Jurgėla) was established on 1 June 1944.At the end of the Second World War, the ALT faced the new issue of political émigrés or Displaced Persons. lt worked to achieve a favourable decision by the administration, which would give them entry into the country. Thanks to the ALT’s efforts, a law was passed setting a quota for exiled people from the Baltic states and eastern Poland on 19 June 1948. Following the 16 September 1948 meeting between the ALT and President Truman in the White House, it became clear that Lithuania’s liberation would be protracted. The ALT was determined to carry it out patiently. It published memoranda for the administration and organised demonstrations, in this way attracting the attention of the administration and the public.At that time close cooperation between the ALT and the Supreme Committee for the Liberation of Lithuania (WLEIK) developed in the process of building up Lithuania's case. There were signs of cooperation between political organisations in all the Baltic states. Joint political statements were published, and marches were held in protest against the occupation of the Baltic states (such as the 4 March 1948 demonstration against the Soviet Union organised by people from the Baltic states in New York).
Keywords: Soviet occupation; USA; emigree; emigree organizations; Lithuanian American Council